2015
DOI: 10.1111/jar.12224
|View full text |Cite
|
Sign up to set email alerts
|

Screening Prisoners for Intellectual Disabilities in Three English Prisons

Abstract: It is argued that it is feasible to screen for intellectual disabilities in prisons and, given the inequalities to which prisoners with intellectual disabilities are subject in prison, it is time for such screening to be rolled out to all prisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 28 publications
(47 reference statements)
2
47
0
Order By: Relevance
“…To conclude, a large percentage of this study's sample of police suspects suffered from intellectual disability (Gudjonsson et al, ; Hayes et al, ; Murphy et al, ; Parton et al, ; Søndenaa et al, ; Young et al, ). Pending future research on the prevalence of intellectual disabilities in Dutch police suspects and on the impact of both cognitive and practical aspects of intellectual disability on functioning within the interrogation room, we hope our study contributes to raising awareness among police interrogators that it is quite likely they will run into suspects with intellectual disabilities on a regular basis and that they need to take special precautions when interrogating them (Gudjonsson & Joyce, ; Herrington & Roberts, ; Scheyett et al, ).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…To conclude, a large percentage of this study's sample of police suspects suffered from intellectual disability (Gudjonsson et al, ; Hayes et al, ; Murphy et al, ; Parton et al, ; Søndenaa et al, ; Young et al, ). Pending future research on the prevalence of intellectual disabilities in Dutch police suspects and on the impact of both cognitive and practical aspects of intellectual disability on functioning within the interrogation room, we hope our study contributes to raising awareness among police interrogators that it is quite likely they will run into suspects with intellectual disabilities on a regular basis and that they need to take special precautions when interrogating them (Gudjonsson & Joyce, ; Herrington & Roberts, ; Scheyett et al, ).…”
Section: Resultsmentioning
confidence: 78%
“…However, we found that 28.7% had an IQ below 70, which is a much higher percentage than previous studies in police suspects, who found that 8.6% (Gudjonsson et al, ) and 6.7% (Young et al, ), respectively, had an IQ below 70. Previous studies performed in adjucated prisoners in the United Kingdom found that 16.4% had an IQ between 70 and 79 (Hayes et al, ) and that about 7% had an IQ below 70 (Hayes et al, ; Murphy, Gardner, & Freeman, ). Furthermore, 83.4% of our sample had an IQ below 85.…”
Section: Discussionmentioning
confidence: 94%
“…The screening tool has been applied in several studies in GB during the last few years [12]- [14] with adequate validity in contrast to findings from the present study. The usefulness of the LDSQ in a Norwegian setting does not seem to be as good, and is thus not recommended until after it has been examined further.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, our findings highlight the importance of intellectual disability screening and identification within the criminal justice system. Identification of intellectual disability in this population is a prerequisite for access to intellectual disability‐specific services in prison and critical to enhancing continuity of care through integration with intellectual disability‐specific services during and after the transition from prison to community (Murphy et al ). Furthermore, prisoners with unidentified mild to borderline intellectual disability are highly vulnerable, and identifying, targeting and supporting their unmet needs post‐release should be a public health priority (McBrien ).…”
Section: Discussionmentioning
confidence: 99%